Respuesta :

Answer:

a)-4   b)2

Step-by-step explanation:

a) if f(-2) then sub in -2 to the equation

so 3(-2)+2

   = -6+2

   = -4

b)   make f(x) equal to 8. f(x) is 3x+2 so..

       3x+2=8

          3x=6

           x=2

hope it helps :)

Answer:

a) [tex]f(x)=-4\\[/tex]

b) [tex]x=2[/tex]

Step-by-step explanation:

a) plug in –2 for x

[tex]f(x)=3x+2\\f(-2)=3(-2)+2\\f(-2)=-6+2\\f(-2)=-4[/tex]

b) set the equation equal to 8 and solve for x

[tex]f(x)=3x+2\\8=3x+2\\8-2=3x+2-2\\6=3x\ \\2=x[/tex]